A study of the impact of project-based learning on student learning effects: a meta-analysis study - Zhang, Lu; Ma, Yan (Frontiers in Psychology, 2023)
With the educational reform for skills in the 21st century, a large number of scholars have explored project-based learning. However, whether project-based learning can effectively improve the learning effect of students has not yet reached a unified conclusion. This study uses a meta-analysis method to conduct an in-depth quantitative analysis of 66 experimental or quasi-experimental research papers based on project-based learning over the past 20 years. The results of the study showed that compared with the traditional teaching model, project-based learning significantly improved students' learning outcomes and positively contributed to academic achievement, affective attitudes, and thinking skills, especially academic achievement. The results of the moderating effects test indicated that the effectiveness of project-based learning and teaching was influenced by different moderating variables, including country region, subject area, type of course, academic period, group size, class size, and experimental period.: (1) from the perspective of country geography, the effects of project-based learning in Asia, especially in Southeast Asia, were significantly better than those in Western Europe and North America; (2) in terms of curriculum, project-based learning promotes student learning effects more significantly in engineering and technology subjects, and is better applied in laboratory classes than in theory classes; (3) from a pedagogical point of view, project-based learning is more suitable for small group teaching, in which the group size is 4-5 people teaching the best results; (4) in view of the experimental period, 9-18 weeks is more appropriate and has more obvious advantages for application at the high school level.